The low cost apartment for wheelchair user - Gunawan Tanuwidjaja; Jocelin Marchelina; Valerie Layni Y; Joyie Joyie; Arina Hayati (IPTEK Journal of Proceedings Series, 2017)
The low-cost apartment concept was prescribed by Government to supply residential needs. The persons with disability (PwD), constituting 0.74% of Indonesian in 2000, (Badan Pusat Statistik Indonesia, 2001) also needed the housing provision. In Surabaya, approximately five thousand (5000) PwD were documented in 2010 or 0.1% from total population (Badan Pusat Statistik Kota Surabaya, 2014). Therefore, the accessible low-cost apartment concept was needed for the provision. The 36-sqm-apartment design would cater person with a disability (a wheelchair user) and spouse were designed with five principles of inclusive design of (Tanuwidjaja, Laurens, Sulendra, & Erandaru, 2016). The design was conducted with the participatory design process and several workshops with many users spectrum (wheelchair users, blind and deaf persons). The principles implemented in the design were: User-Centered, Equitable Use but Reasonable Use, Simple and Intuitive Use, Low Physical Effort, and Prohibition of Usage Error. The five principles were implemented inaccessible doors, reachable spaces, and furniture, as well as accessible toilets. All these ensures that the apartment unit to become accessible.